2021
DOI: 10.1038/s41467-021-21435-6
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial engineering of Bi2S3/Ti3C2Tx MXene based on work function for rapid photo-excited bacteria-killing

Abstract: In view of increasing drug resistance, ecofriendly photoelectrical materials are promising alternatives to antibiotics. Here we design an interfacial Schottky junction of Bi2S3/Ti3C2Tx resulting from the contact potential difference between Ti3C2Tx and Bi2S3. The different work functions induce the formation of a local electrophilic/nucleophilic region. The self-driven charge transfer across the interface increases the local electron density on Ti3C2Tx. The formed Schottky barrier inhibits the backflow of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(167 citation statements)
references
References 47 publications
4
163
0
Order By: Relevance
“…81 Addition of graphene or its derivatives to MXenes can further boost the photo-thermal properties of the resulting composites, which could lead to enhanced healthcare applications of MXenegraphene composites. Recently, Li et al 82 have developed Bi 2 S 3 / Ti 3 C 2 T x MXene Schottky junctions and carried out interface engineering based on work function. The engineering of work function helps to enhance the charge transfer and hence photocatalytic activity, which resulted in fast killing of the bacteria.…”
Section: Photo-thermal and Photocatalytically Driven Sterilizationmentioning
confidence: 99%
“…81 Addition of graphene or its derivatives to MXenes can further boost the photo-thermal properties of the resulting composites, which could lead to enhanced healthcare applications of MXenegraphene composites. Recently, Li et al 82 have developed Bi 2 S 3 / Ti 3 C 2 T x MXene Schottky junctions and carried out interface engineering based on work function. The engineering of work function helps to enhance the charge transfer and hence photocatalytic activity, which resulted in fast killing of the bacteria.…”
Section: Photo-thermal and Photocatalytically Driven Sterilizationmentioning
confidence: 99%
“…Synergistic killing of bacteria by combining the photodynamic activity of GO and the photocatalytic activity of Ag-NPs (GO/Ag/collagen coating) under laser irradiation resulted in high bacterial efficiency against E. coli (96.3%) and S. aureus (99.4%) reported by Xie et al (2017) . Li J. et al (2021) Designed nanoparticles embedded at the semiconductor metal interface called the interfacial Schottky junction of bismuth sulfide (Bi 2 S 3 ) and titanium carbide (Ti 3 C 2 T x ) nanosheets that exhibited photocatalytic activity resulting in the eradication of S. aureus (99.86%) and E. coli (99.92%) under NIR irradiation.…”
Section: Potential Cytotoxicities Associated With Photothermally Active Nanomaterials and Strategies To Minimize Themmentioning
confidence: 99%
“…MXenes are expected to be resistant to biofouling and offer bactericidal properties [91]. However, very few studies [91][92][93][94][95][96][97][98][99] have been carried out in this direction. An initial work by Rasool et al [97] reported that Ti 3 C 2 Tx membranes could be an ideal platform for antibacterial studies (Figure 5a-d).…”
Section: Antibacterial Activity Of Mxene-based Membranesmentioning
confidence: 99%
“…They also demonstrated the outstanding bioactive properties of Ti 2 C and Ti 3 C 2 MXenes against a Gram-negative bacterial strain [99]. Recently, Zhu et al [95] evaluated the effect of near-infrared (NIR) light on the antibacterial activities of silver (Ag), Ti 3 C 2 T x , and an Ag/Ti 3 C 2 T x composite. The as-prepared Ag/Ti 3 C 2 T x composite showed a high efficacy against Gram-positive S. aureus and Gram-negative E. coli bacteria in an in vitro antibacterial test.…”
Section: Antibacterial Activity Of Mxene-based Membranesmentioning
confidence: 99%